STEAM Approach: A Classroom Action Research as an Effort to Increase Early Childhood Creativity - Syabudin Gade (Barkah Publishing, 2024)
Every early childhood has different development. This development can be given intervention in several aspects. One aspect of development that can be intervened in the development of early childhood is the aspect of creativity. This study aims to improve the creativity of early childhood by implementing the STEAM approach. This study is a classroom action research with the Kemmis & Mc Taggart design using four steps, namely planning, action, observation and reflection. The subjects of this study were kindergarten students. Data were obtained using observation and test techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the STEAM approach can improve the creativity of kindergarten students